MdMyb93 is a regulator of suberin deposition in russeted apple fruit skins. Issue 4 (15th September 2016) - Legay, Sylvain; Guerriero, Gea; André, Christelle; Guignard, Cédric; Cocco, Emmanuelle; Charton, Sophie; Boutry, Marc; Rowland, Owen; Hausman, Jean‐Francois
Summary: A comparison of the transcriptomes of russeted vs nonrusseted apple skins previously highlighted a tight relationship between a gene encoding an MYB‐type transcription factor, MdMYB93, and some key suberin biosynthetic genes. The present work assesses the role of this transcription factor in the suberization process. A phylogenetic analysis of MdMYB93 and Arabidopsis thaliana MYBs was performed and the function of MdMYB93 was further investigated using Agrobacterium ‐mediated transient overexpression in Nicotiana benthamiana leaves. An RNA‐Seq analysis was performed to highlight the MdMYB93‐regulated genes. Ultraperformance liquid chromatography–triple time‐of‐flight (UPLC‐TripleTOF) and GC‐MS were used to investigate alterations in phenylpropanoid, soluble‐free lipid and lipid polyester contents. A massive accumulation of suberin and its biosynthetic precursors in MdMYB93 agroinfiltrated leaves was accompanied by a remobilization of phenylpropanoids and an increased amount of lignin precursors. Gene expression profiling displayed a concomitant alteration of lipid and phenylpropanoid metabolism, cell wall development, and extracellular transport, with a large number of induced transcripts predicted to be involved in suberin deposition. The present work supports a major role of MdMYB93 in the regulation of suberin deposition in russeted apple skins, from the synthesis of monomeric precursors, their transport, polymerization, and final deposition as suberin in primary cell wall.